Credit supply, homeownership and mortgage debt - Taşkın, Ahmet Ali; Yaman, Fırat (Journal of Housing Economics, 2023)
We analyze the effect of credit supply on households’ homeownership and home equity outcomes. Banking deregulation together with states’ autonomy to limit deregulation provides an exogenous shift in credit supply which shows variation across states and time. We find that a shift from full to no regulation increases the probability of homeownership by one percentage point, and of having a mortgage by two percentage points, explaining up to 43% of the increase in homeownership and the share of households with mortgages. Mortgage debt increases by up to 20%. Household leverage and debt exposure measured as debt to income ratio increase slightly for households outside of MSAs.
CRIS-Team Scopus Importer:2023-06-30
Keywords: Banking deregulation; Credit supply; Homeownership; Household debt; Household finance; Housing demand; Mortgage